(untitled) (Baghdad Science Journal, 2024)
Binahong (Anredera cordifolia) leaves contain chemical compounds that can be used to promote anti-obesity. This study aimed to examine the phytochemical and anti-obesity properties of the ethanol extract of binahong leaves. The binahong extract was obtained by maceration of the leaves, followed by ethanol extraction. Phytochemical analysis was performed by UV-Vis spectroscopy to identify and determine the levels of flavonoids, phenolic compounds, alkaloids, and tannins in the extract, using quercetin as a standard for calibration. Absorbance was measured at a wavelength of 430 nm. The flavonoid, glycoside, tannin, saponin, and steroid/terpenoid contents were determined, but alkaloid compounds were not found. The conclusion is, that the large flavonoid content (14.9385 mgQE/g) in the binahong leaf extract has potential to provide anti-obesity effects.